High School History Teachers' Perceptions of the Teacher Competency Test (UKG) in Binawidya and Tuah Madani Districts - Alrizki, Marisa Tito; Isjoni, Isjoni; Asril, Asril (CV. Rayyan Dwi Bharata, 2024)
Every history teacher has the ability or competence as a teacher. The government created a skills testing program called the Teacher Competency Test (UKG). This research aims to determine the perceptions of high school history teachers regarding the Teacher Competency Test (UKG) in Binawidya and Tuah Madani Districts, Pekanbaru City. This study uses a qualitative method. Data was collected through observation, interviews and documentation. The subjects of this research were 6 teachers in the field of History at the high school level in Binawidya and Tuah Madani Districts, Pekanbaru City who had passed the UKG. Data analysis techniques use data reduction, data presentation, data verification and drawing conclusions. The results of research on High School History Teachers' Perceptions of the Teacher Competency Test (UKG) in Binawidya and Tuah Madani Districts are that teachers think they have various kinds of obstacles during UKG, such as problems with questions that are considered difficult, inadequate facilities and infrastructure for remote areas and a lack of socialization regarding the Competency Test program. This teacher means that in 2024 the government will have overcome this problem by forming a Regional/Ministry/Other Institution Competency Test team. These teams have members who have played a role according to their use, such as a Helpdesk which helps provide solutions to problems experienced during the Competency Test. The purpose of holding this UKG is to map teacher abilities and to meet the requirements for appointment to functional positions through transfer from other positions, promotion and re-appointment to functional positions. With the evaluation results obtained by teachers in the form of certificates and letters of recommendation, which are important and useful for their functional position.